Mössbauer Effect Studies of Fe–Base Alloys during Mechanical Alloying and Grinding (Overview) - Cabrera, Alejandra Fabiana (1995)
Mossbauer effect studies of mechanical alloying and mechanical grinding of Fe-B, Fe-Sn and Fe-TM-Al (TM = Ni, Cu), complemented by X-ray diffraction analysis are presented. Some of these systems (Fe-Sn) are especially suited for these type of research because the environments of both elements can be probed. In all cases powders were processed with a Retsch MM 2 horizontal vibratory mill under argon atmosphere. In Fe 1-x Sn x (0.15 ≤ x ≤ 0.40), the evolution of mechanical alloying with time and the dependence of the stationary state with composition were investigated. An intermediate superparamagnetic FeSn 2 state and a stationary bcc solid solution with composition fluctuations were inferred from the Mossbauer spectra. Solubility of tin into bcc iron was found to be extended up to a maximum of about 22 at.%. Pure powder mixtures of nominal composition Al 75 Ni 10 Fe 15 , Al 65 Ni 20 Fe 15 and Al 63 Cu 25 Fe 12 have been mechanically alloyed. Stable disordered crystalline phases were obtained after milling and, in some cases, the partial ordering of bcc structures induced by milling was observed. Further annealings did not produce structural changes but removed the remaining disorder. The characteristic quadrupole interaction parameters were obtained by Mossbauer spectroscopy. The evolution of Fe 2 B with grinding time was studied. The first milling stage was characterized by fragmentation and accumulation of strain. On further processing, segregation of α-Fe occurred while grain size reduction continued and strain was partially removed. For longer grinding times separation of α-Fe proceeded at an almost steady rate. Two additional experiments designed to reduce and increase oxygen contamination let us tentatively discard this element as the main responsible for the observed decomposition.